Questions to Ask Before Agreeing to Surgery - Carolyn S. Wilken (EDIS, 2005)
All surgeries have risks and benefits. As the patient, you need to ask questions prior to surgery, especially elective surgery (an operation you choose to have performed). If your procedure is an emergency surgery, you will still want to get as many of these questions answered as possible. You can also inform your health care surrogate to be prepared to ask these questions for you. This document is FCS2235, one of a series of the Department of Family, Youth, and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: June, 2005.